A Contemporary Review of the Operations Management in Handling Major Oil Spills from Ships and Tankers in the Straits of Malacca, Malaysia - Taib, Che Azlan; Ismail, Md. Badron (Sustainable Marine Structures, 2025)
Operations Management (OM) plays a critical role in managing oil spills from tankers, specifically in the Straits of Malacca (SOM), Malaysia. Ineffective decision-making and outdated operational practices have historically led to significant environmental damage, endangering marine ecosystems and resources due to the activities of international shipping. Global experiences with tanker-related oil pollution disasters indicate that full recovery of spilled oil is rarely achieved, due to a combination of natural and physical constraints, a trend also observed in the SOM. Effective OM in this context requires a multidisciplinary approach involving experts in engineering, chemistry, biology, marine navigation, environmental economics, law, and the social sciences. These diverse inputs inform the development of comprehensive frameworks, including legal, institutional, and operational, which are integrated into the National Oil Spill Contingency Plan (NOSCP). The NOSCP outlines preparedness and response strategies, the strategic distribution of oil spill response equipment (OSRE), and the standard operating procedures (SOPs) to manage and sustain effective responses to future oil spill incidents in the SOM. It is a high time for the Malaysian authority to opt for a single agency to manage the major oil spill in the SOM for better operational efficiency and cost-effectiveness. ER